Legal Standards Provided by the Council of Europe and the Case-Law of the European Court of Human Rights - Tóth, Barbara (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:The European Convention on Human Rights (ECHR) and the European Court of Human Rights (ECtHR) play a significant role in protecting and promoting children’s rights in Europe. Despite the limited explicit references to children’s rights in the ECHR, the ECtHR has developed a substantial body of case law dealing with children’s rights, frequently referencing the UN Convention on the Rights of the Child (CRC). The dynamic character of the ECHR and its interpretative approaches have contributed to its growing impact on the development of children’s rights in Europe, especially when consistent with other international and European instruments. The Council of Europe (CoE) has made protecting children’s rights and promoting child-friendly justice a priority, aligning with the principles of the CRC and addressing this issue in its conventions, action plans, guidelines, and handbooks. Keywords: Council of Europe, ECHR, ECtHR, best interest of the child, right to be heard, right to participation in proceedings